Puerarin Inhibits Nasopharyngeal Carcinoma Cell Growth by Inducing Ferroptosis with Involvement of the SLC7A11/GSH/GPX4 Axis - Lifeng Jia; Xiufu Liao; Xiang An; Aied Mohammed Alabsi; Zhongwan Li; Chunmei Li (Journal of Pharmaceutical Innovation, 2027)

Context-dependent functionality of 2′-fucosyllactose with Bifidobacterium breve M-16 V and short-chain galacto−/long-chain fructo-oligosaccharides in infant gut fermentation - Wenbo Guo; Binghui Zhou; Youlan An; Huiying Qiu; Lintao Zhang; Xianfeng Zhao; Xinyu Li; Bowen Shi; Ao Liu; Xiaoze Pang; Zhe Wang; Xinjie Zhu; et al. (Food Research International, 2026)

Kaolin-reinforced green polymeric membrane for sustainable desalination - Min Wei Boey; Xiaomeng Hu; Xiaolu Li; Jiawei Sun; Xinxin Wei; Mingyi Jia; Shauhrat S. Chopra; Sai Kishore Ravi; Alicia Kyoungjin An (Desalination, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Molecular hydrogen mitigates hydroxyl radical–driven oxidative deterioration of tilapia myofibrillar proteins: through the lens of redox microenvironment modulation - Zhuo-Feng Gan; Jia-Ying Li; Ying-Zhi Yao; Hui-Min Lu; Xi-Yang Chen; Ming-Shen Zhu; Duried Alwazeer; Xin-An Zeng; Lan Liao (Food Chemistry, 2026)

Triazine and other herbicides in sediments of lower Laurentian Great Lakes – pre- and post-depositional mobility and in-situ degradation - Shanshan Zhou; Huan He; Tian Lin; Jiehong Guo; Xiusen Yang; Xinyue Jia; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Environmental Pollution, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Screening of attractants based on the interaction between three odorant-binding proteins and mung bean volatiles in Callosobruchus chinensis - Zi-Qing Wang; Jia-Hao Zan; Jin-Ze An; Wen-Wen Zhu; Meng-Meng Kuang; Qi Zhu; Xiao-Ming Li (Journal of Stored Products Research, 2026)

Protective Effects of Double-layered Multinucleated Microcapsules Containing Bifidobacterium adolescentis FS2-3 Against Enteritis Mediated by Different Pathogens - Jiayi Tang; Henan Zhang; Danli Yan; Tong Li; Zijing Li; Yulian Zhao; Ying Wang; Feiyu An; Jia Guo; Kexin Zheng; Natalia Alekseevna Golovneva; Junrui Wu; et al. (Probiotics and Antimicrobial Proteins, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Two stages of Sn enrichment in granitic magmatism: insights from Sn isotopes of cogenetic minerals - Jia-Xin She; Weiqiang Li; Ru-Cheng Wang; Lei Xie; Chen Liu; Zhihao Xu; Shichao An; Cheng Xu (Geochimica et Cosmochimica Acta, 2026)

Cyprinid herpesvirus 2 (CyHV-2) ORF53 inhibits NF-κB signalling by targeting p65 degradation - Chuan Yun Zhang; Zheng Liu; An Ning Pang; Jia Yi Li; Bo Li; Nan Li; Lan Hao Liu; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Climate-driven diversity patterns and range dynamics of Maclura (Moraceae) worldwide based on the MaxEnt model - Kexin Zhao; Lei Wang; Guodong Li; Yilong Shi; Cancan Li; Lehan Jia; Jinan An; Yawen Zhang; Qiaoming Zhang (Flora, 2026)

A 3D Ubiquitous Multiple Joint Model for stability analysis in large underground caverns within jointed rock masses - Bo Ni; Qin Chen; An-chi Shi; Jia-wen Zhou; Hai-bo Li (Computers and Geotechnics, 2026)

Three-dimensional modeling reveals lateral recharge dominates seasonal dynamics of dry soil layers under exotic vegetation on the Loess Plateau - Zhengyu Li; Xiao Bai; Chenggong Liu; Xiaoxu Jia; Chunlei Zhao; Ming'’an Shao (CATENA, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Deciphering potential significances of biliary microbiome in cholelithiasis and cholangiocarcinoma - Guangchao Liu; Kangxu Chen; Jiali Li; Kaifeng Zhang; Guanglin Niu; Yu Ding; Yunzhi Lv; Qiwen Tian; Zhenxi Cao; Haiqiang Wang; Junru Jia; Guosen Zhang; et al. (Antonie van Leeuwenhoek, 2026)

Chlorfenapyr adversely influences the survival rate and pest control capability of ichneumonid Campoletis chlorideae - Ningbo Zhang; Shengyi Wang; Haobo Li; Yunxing Jia; Jiaxin Zhao; Junkai Zhang; Guang Yang; Jizhen Wei; Shiheng An; Sufen Bai (Pesticide Biochemistry and Physiology, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

Four new flavonoids from Sophora flavescens and their antibacterial activities - Yun Gao; Xin-Min Li; Fan-Fan Cao; Guo-Qing Long; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

Interfacial synergy-enhanced catalysis in hierarchically confined poly (glycidyl methacrylate) @ZIF-8@Au composite microspheres for p-nitrophenol degradation - Jian-Bo Qu; Guo-Yu Yue; Jian-Ling Zhang; Yuan Yang; Dong Wang; Jia-Le An; Jing Li (Journal of Environmental Chemical Engineering, 2026)

Thermodynamic promotion of iron reduction by sulfide facilitates vivianite formation under high Fe/P ratio Conditions - Jiamin Jia; Yan Gao; Feng-Ai Yang; Jifei Chang; Xiaoming Yang; Jingkun An; Danhui Liang; Xin Wang; He Li; Jun Huang; Nan Li (Journal of Environmental Sciences, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

Whole genome sequencing reveals transmission dynamics and persistence of Listeria monocytogenes along the poultry slaughtering and processing chain - Ye Wang; Chaohui Huang; Sijie Wu; Jianye Jia; Tianxiang Pan; Ruochen Wang; Jing Li; Zegang Wang; Chuang Meng; Yuelan Yin; Xin'an Jiao (International Journal of Food Microbiology, 2026)

Hydrothermal stress influences the spatial distribution pattern of soil organic carbon and its stock in Xinjiang - Yunhao Li; Mingjie Shi; Ping'an Jiang; Jinzhi Gu; Jia Guo; Jiahao Zhao; Gongxin Wang; Yanmin Fan; Hongqi Wu (CATENA, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hydrogen distributions during thermal maturation of organic-rich sedimentary rocks: Generation potentials and influencing factors of hydrogen-bearing gases revealed by pyrolysis - Xiaodong Liu; Wanglu Jia; Qiang Wang; Jinbu Li; Jian Chen; Ping'an Peng (International Journal of Coal Geology, 2026)

Dynamic multimodal fusion for power load forecasting: A dual-stream deep learning architecture with ICEEMDAN decomposition and attention-enhanced nonlinear mapping - Zhipeng Luo; Li Fan; Wenchao Jia; Bin Gong; Aimin An (Energy and Buildings, 2026)

Isolation and antibacterial activity of three new flavonol compounds from Sophora flavescens - Si-Han Wang; Xiang-Yu Zhao; Zhi-Kang Chen; Yun Gao; Xin-Min Li; Ya-Juan Gao; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

A persistently active fast radio burst source embedded in an expanding supernova remnant - Chen-Hui Niu; Di Li; Yuan-Pei Yang; Yuhao Zhu; Yongkun Zhang; Jia-Heng Zhang; Zexin Du; Jumei Yao; Xiaoping Zheng; Pei Wang; Yi Feng; Bing Zhang; et al. (Science Bulletin, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Rational design and synergistic optimization of 2D COF nanofiltration membranes: A review - Tianqi Jia; Zhao Zheng; Leilei Hou; Zhixiang Li; Xueqing Ma; Xinru An; Xia Zhan (Journal of Environmental Chemical Engineering, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Coplanar DCA-based hypofractionated stereotactic radiotherapy for very small brain metastasis from non-small cell lung cancer: treatment planning comparison with coplanar VMAT and preliminary clinical outcome - Shipai Zhu; An Li; Jia Liu; Qin Deng; Qingfang Li; Jialu Lai; Lin Zhou (Physical and Engineering Sciences in Medicine, 2025)

Botryosphaeria dothidea causes leaf spot disease on Rosa roxburghii in China - Qinyi Hu; Taotao An; Wei Jia; Junxian Chen; Ying Xu; Zhu Li; Haixia Ding (Crop Protection, 2025)

Main controls on nitrogen cycling and Mo-U enrichment of the Middle Triassic Chang 7 Member in the Ordos Basin: Implications for redox and ultra-organic enrichment in a giant highly productive lake - Chuhan Zhao; Xiaodong Liu; Wanglu Jia; Wenzheng Zhang; Jian Chen; Jinbu Li; Ping'an Peng (Marine and Petroleum Geology, 2025)

Highly selective and sensitive colorimetric and fluorescence detection of copper(II) and glyphosate using dual-functional peptide probe and its multifarious applications in food sample analysis and bioimaging - Peng Wang; Shiyang Li; Chunmei Pu; Xinlin Cao; Mengying Jia; Jiaxiang Ai; Yumei Yue; Rige Biqume; Yong An (Food Chemistry, 2025)

Integrated proteomic, chemical forms, and distribution analysis reveals NaCl-mediated detoxification of cadmium in Suaeda salsa - Honglei Jia; Shutong Wang; Jie Xu; Fengyun Yao; Wen Yuan; Haodong An; Jisheng Li; Chengtao Li (Plant Cell Reports, 2025)

Optimisation of the flash extraction process for male catkins of Corylus heterophylla and evaluation of their oxidative stress resistance - Fang Mo; Jia Li; Jian Gao; Jun Jiang; Renbo An (Natural Product Research, 2025)

Identifying the origin of Laggera crispata (Vahl) Hepper & J. R. I. Wood based on UPLC fingerprinting and chemometrics - An Wang; Songmei Li; Xiaoyun Tong; Jia Qiu; Dianfei Ma; Jie Xia (Natural Product Research, 2025)

Harnessing built-in electric fields for enhanced electron transfer in biosensor for precise digital health assessment - Tian-Run Lv; Yaqiong Yang; Jia-Chen Zhang; Ling Qi; Ming-Jie Yin; Yong Li; Ken Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2025)

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Corrigendum to ‘Quantification of free and adsorbed fluid content in shale oil reservoirs: Insights from preserved cores and different methods’ [Mar. Petrol. Geol. 177 (2025) 107400] - Hongrui Zhang; Jinbu Li; Wanglu Jia; Min Wang; Ping'an Peng (Marine and Petroleum Geology, 2025)

Ice ball size and temperature change during cryoablation in a lard and an ethiodized-oil tissue phantom - Nai-Wen Chang; Shu-Huei Shen; Chien-An Liu; Felix Antony Halim; Jia-An Hong; Chih-Chien Li; Ping-Lang Yen (Cryobiology, 2025)

Rational hapten design, monoclonal antibody preparation, and immunoassays development for rapid detection of fomesafen in agricultural products and soil - Qingqing Gao; Jingqian Huo; Chang Wang; Jiayu Cao; Haijiao Dong; Jia Kang; Kaiwen Li; Zexiu An; Lai Chen; Jinlin Zhang (Food Chemistry, 2025)

Isolation and identification of Diaporthe phoenicicola causing leaf spot on Rosa roxburghii in China - Junxian Chen; Liangyu Xiao; Taotao An; Wei Jia; Qinyi Hu; Ying Xu; Zhu Li; Haixia Ding (Crop Protection, 2025)

Quantification of free and adsorbed fluid content in shale oil reservoirs: Insights from preserved cores and different methods - Hongrui Zhang; Jinbu Li; Wanglu Jia; Min Wang; Ping'an Peng (Marine and Petroleum Geology, 2025)

Geochemical characteristics of light hydrocarbons generated in thermochemical sulfate reduction: Results from three series of simulation experiments - Zhenyu Sun; Jian Chen; Wanglu Jia; Qiang Wang; Jie Xu; Xin Li; Jianghu Yang; Ping'an Peng (Marine and Petroleum Geology, 2025)

A comprehensive investigation of bacterial communities in sediment and bulk water in a chlorinated drinking water distribution system - Dong Hu; Xiang Li; Kang An; Xin Zhang; Minjia Zheng; Peng Li; Long Ji; Ruibao Jia (Environmental Research, 2025)

Cleaner purification of contaminants on cotton substrate interfaced with supercritical carbon capsules for sustainable development in cleaning industries - Meng-Yue Li; Fan Wang; An-Tong Liu; Qing-Cheng Tang; Xue Dong; Jia-Jie Long (Process Safety and Environmental Protection, 2025)

Chemical composition, antibacterial and antioxidant activities of Sanghuangporus baumii fermented cultures - Xiao-Dan Zheng; Meng-Jia Pu; Zi-Feng Guo; Ying Li; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Reconstruction of surface defects in Bi2MoO6 induced by amorphous ZnO for ultra-fast photocatalytic purification of Cr(VI) - Li-li Yao; Cheng-zhao Jin; Xin-an Yang; Wang-jia Xia; Wang-bing Zhang (Journal of Environmental Chemical Engineering, 2025)

Pilot-scale rotor device with low acid-site zeolite for rapid adsorption–desorption of polymerizable VOCs - Huifang Wu; Wenjing Zhang; Lisha Miao; Kan Li; Haoxuan Liu; Weili Zhu; Zeyao An; Yanfeng Tang; Lizhong Liu; Jinping Jia (Chemical Engineering Journal, 2025)

Characteristics of Humic Acid–Iron Colloid Stability and Its Mechanism of Binding with As(III) - Junfeng An; Conghui Wang; Jia Yu; Kaipian Shi; Youru Yao; Jingyi Zhang; Chonghong Zhang; Yuesheng Lin; Shiyin Li (Bulletin of Environmental Contamination and Toxicology, 2025)

Interaction Between Hypoxia-Inducible Factor 1-alpha Gene Polymorphism and Helicobacter pylori Infection on Gastric Cancer in a Chinese Tibetan Population - Su-Hua Li; Yan Li; Meng-Jun Zhang; Qi An; Jia-Nan Tao; Xue-Hong Wang (Biochemical Genetics, 2025)

Restraining thermal runaway in lithium-ion batteries: A computational model using mini-channel flow boiling for enhanced safety - Honglei Ren; Li Jia; Liaofei Yin; Chao Dang; Zhoujian An; Zhifeng Chen (Process Safety and Environmental Protection, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

Multiomics analysis revealed the effects of polystyrene nanoplastics at different environmentally relevant concentrations on intestinal homeostasis - Jian-Zheng Yang; Ji-Hui Li; Jia-Li Liu; An-Ding Zhou; Hui Wang; Xiao-Li Xie; Kai-Kai Zhang; Qi Wang (Environmental Pollution, 2025)

Selective removal of mercury ions from aqueous solution by thiourea-functionalized porous aromatic framework - Zi-Xuan Jin; He-Jie Lu; Xiang-Wen Chen; Yi-Hang Li; Si-Chao Zhu; Xiu-Lei Li; Zhi-Qian Jia; Yuexin Guo; Yu Yang; Li-An Hou (Desalination, 2025)

Tree-level carbon stock estimations across diverse species using multi-source remote sensing integration - Qing Li; Jia Yin; Xiaoxin Zhang; Dalei Hao; Matheus Pinheiro Ferreira; Wenhui Yan; Ye Tian; Da Zhang; Shen Tan; Sheng Nie; Tianyu An; Xiaoyao Li; et al. (Computers and Electronics in Agriculture, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

Impact of vortex structures on fish hydrodynamics and fluid environment response analysis - Yiyun Peng; Min Chen; RuiDong An; Jia Li (Ocean Engineering, 2025)

Storm deposit characteristics and orbital cyclicity of the Early Devonian Xiejiawan Formation in the Longmenshan area, Sichuan Province, China - Fengjie Li; Zheng’an Chen; Sanem Acikalin; James G. Ogg; Shannon Flynn; Gengchuan Liu; Pengfei Zhang; Jia Wang; Anqing Chen; Mingcai Hou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Walnut shell-based composite fillers to enhance two-stage biological aerated filter for efficient nitrogen removal: Carbon source slow-release properties, regulatory strategies and microbial response characteristics - Linhua Xie; Shuxin Wang; Qiong Fan; Xiaoli Lei; Jia Li; Dan An; Chuanchuan Zhao; Yuqin Wang (Journal of Environmental Chemical Engineering, 2025)

Influence of roughness and slip velocity on the evolution of frictional strength - Quan Gan; Xinyuan Zhang; Qiang Li; Jianye Chen; Fengshou Zhang; Zhen Zhong; Yunzhong Jia; Pengliang Yu; Mengke An; Derek Elsworth (International Journal of Rock Mechanics and Mining Sciences, 2025)

Two rare C14-C15 chemical bond-breaking 7/5/5 skeleton schinortriterpenoids and their neuroprotective activities of against CORT-induced apoptosis of PC12 from the Schisandra chinensis leaves and stems - Jian Li; Yong-Guo Li; Yong-Cheng Yang; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2025)

Driving risk assessment in exit areas of highway tunnels based on driving behavior characteristics: Methods and case studies - Bo Liang; Shuangkai Zhu; Haonan Long; Jia An Niu; Can Qin; Haoming Li (Tunnelling and Underground Space Technology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Congested heptacyclic meroterpenoids with anti-SARS-CoV-2 and anti-inflammatory activities from mangrove endophytic fungus Talaromyces amestolkiae SCNU–F0041 - Jialin Li; Hao Jia; Chen Chen; Shu An; Jianchen Yu; Jie Yuan; Yuhua Long; Mengfeng Li (Phytochemistry, 2025)

Resistance and propulsion trade-offs induced by different morphologies: Insights for fish conservation - Lin Sun; Jia Li; Min Chen; ChingHao Yu; Ruidong An (Journal of Environmental Management, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

A forecasting tool for optimized emission control strategies to achieve short-term air quality attainment - Zhaoxin Dong; Shuxiao Wang; Yueqi Jiang; Jia Xing; Dian Ding; Fenfen Zhang; Dejia Yin; Qian Song; Jingyu An; Hongli Wang; Cheng Huang; Qian Wang; et al. (Journal of Environmental Management, 2025)

Dietary Probiotic Rhodopseudomonas palustris Formulation Improves Growth Performance, Muscle Composition, Digestive Enzyme Activity, Non-Specific Immunity and Disease Resistance of Juvenile Ivory Shell (Babylonia areolata) - Xiao Wang; Yao-Peng Lu; Ze-Long Zhang; Pei-Hua Zheng; Jun-Tao Li; Xiu-Xia Zhang; Jia-Jun Li; Heng-Mei Wu; Jian-An Xian (Fishes, 2024)
Rhodopseudomonas palustris (RP) are known anaerobic bacteria with probiotic properties containing several bioactive compounds and enzymes that benefit aquatic animals. However, studies on the use of RP on aquatic animal species are limited. This study investigated the effects of dietary supplementation with RP formulation on the growth, non-specific immunity, and disease resistance of juvenile ivory shells (Babylonia areolata). The experiment was conducted for 8 weeks, with B. areolata fed a control diet (RP0) and four diets containing four different RP formulations, with doses of 1 (RP1), 5 (RP2), 10 (RP3), and 20 (RP4) g/kg, respectively. Higher levels of R. palustris in the formulation led to increased final weight, weight gain, and specific growth rate in B. areolata. The crude protein content was significantly higher in the RP4 group compared to the RP0 group. However, there was no significant difference in the crude lipid content. Higher levels of R. palustris in the RP4 formulation group increased the trypsin and lipase activities. Dietary supplementation with RP significantly increased the total antioxidant capacity, superoxide dismutase, and catalase activities and decreased the malondialdehyde content in B. areolata. Acid phosphatase and alkaline phosphatase activities were significantly increased in the RP4 group compared to the RP0 group. Dietary RP significantly increased the expression levels of antioxidant-related (superoxide dismutase, Cu/Zn-superoxide dismutase, glutathione S-transferase A-like, ferritin) and immune-related (acid phosphatase, cytochrome c) genes. Higher levels of R. palustris in the formulations RP3 and RP4 increased the survival rate of B. areolata challenged with Vibrio parahaemolyticus. These findings indicate that R. palustris preparation could improve growth performance, muscle composition, and digestive capacity and may act as an immune booster for preventing disease in B. areolata.

Influencing factors of hydrogen isotopic fractionation of light hydrocarbons during evaporation and implications - Wenna Liu; Wanglu Jia; Qiang Wang; Jian Chen; Jinbu Li; Ping’an Peng (Organic Geochemistry, 2024)

The protective effect of Auricularia auricula polysaccharides on cyclophosphamide-induced immunosuppression and intestinal injury: A fecal microbiota transplantation study - Tianci Wang; Zikun Jia; Canghai An; Zhibo Wang; Abdul Mueed; Yaqing Liu; He Ma; Lili Guan; Yuting Li; Ling Su (Food Bioscience, 2024)

Unlocking superior preservation: The synergy of lignin and zeolite in chitosan-based composite films for perishable foods - Zhan-Chao Li; Xi Chen; Jia-Li Zhang; Xiao-Ping Gao; Yan-Xia An; Li-Jie Wu; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Packaging and Shelf Life, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Association between phthalates exposure and all-cause mortality among diabetic cases: A prospective study - Xu Cheng; Shiyang Zhang; Jun An; Chengyong Jia; Xin Zhang; Peiwen Li; Youbing Guan; Yan Yan; Zhuoya Zhao; Yuenan Liu; Tao Jing; Suli Huang; et al. (Environmental Pollution, 2024)

Determination and evaluation of canthaxanthin and β-apo-8’-carotenoid ethyl ester in chicken eggs and meat in Tianjin - Xinghua Li; Siyu Yang; Weiyi Jin; Yeqing Jia; Kang An; Jianping Li; Yi Zhang (Food Additives & Contaminants: Part A, 2024)

Genotype–phenotype correlation study of structural abnormalities in a fetal brain caused by a novel KDM4B variant - Xuliang Zhao; Xu Li; Min Yu; Jian-an Jia; Ruixia Tian; Fuxi Zhu (Molecular Biology Reports, 2024)

A highly specific two-photon fluorescent probe for real-time monitoring of acetylcholinesterase in neurogenic disorders in vivo - Weizhen An; Zhongxi Huang; Wei Jiang; Fangning Du; Chenfeng Xu; Qian Shen; Naidi Yang; Jia Zhou; Lin Li; Changmin Yu (Analytica Chimica Acta, 2024)

Calcium chloride seed priming: A dual-action strategy for enhancing Cyrtorhinus lividipennis attraction and deterring brown planthopper infestations in rice - Zhong-Yan Zhu; Xiao-Bao Wu; Jia-jia An; Qian-Qian Deng; Jun Wang; Li-Na Chen; Mao Ye (Crop Protection, 2024)

Manure application enriches phage-associated antimicrobial resistance and reconstructs ecological network of phage-bacteria in paddy soil - Jia-Ying Wang; Xin-Li An; Hong-Mei Zhang; Jian-Qiang Su (Soil Biology and Biochemistry, 2024)

Recent advance for animal-derived polysaccharides in nanomaterials - Meng-na Li; Xiang-ze Jia; Qing-bo Yao; Feng Zhu; Yan-yan Huang; Xin-An Zeng (Food Chemistry, 2024)

Associations between polychlorinated biphenyls and cancer risk among type 2 diabetes: The modifying effects of lifestyle - Peiwen Li; Yu Wang; Qianying Liu; Yan Yan; Zhuoya Zhao; Shiyang Zhang; Chengyong Jia; Jun An; Cheng Xu; Xin Zhang; Tao Jing; Huan Guo; et al. (Chemosphere, 2024)

Hazards of toxic metal(loid)s: Exploring the ecological and health risk in soil–crops systems with long-term sewage sludge application - Shitao Gao; Yanmei Dong; Qingqi Jia; Shuxia Wu; Jiayun Bai; Chao Cui; Ying Li; Peng Zou; Miaoying An; Xinzhong Du; Hongbin Liu (Science of The Total Environment, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Carbon footprint of fresh sea cucumbers in China: Comparison of three aquaculture technologies - Lin Yang; Dong An; Yuhu Cui; Xuexiu Jia; Dong Yang; Wensheng Li; Yanliang Wang; Longjie Wu (Journal of Cleaner Production, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Understanding the extreme differentiation of granitic magmas through elemental geochemistry and Fe isotope signatures - Xiang-Long Luo; Chang-Zhi Wu; Jia-Xin She; Matthew J. Brzozowski; De-Hong Du; Shichao An; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Self-powered broadband photodetectors based on Bi2O2Se with asymmetric contact areas - Xuanyu Ren; Xinyu Li; Xinxin He; Xuyang An; Yang Li; Bo Gao; Feng Gao; Jia Zhang; PingAn Hu (Chemical Engineering Journal, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

Preparation of slow-release carbon source fillers from agricultural solid waste for efficient nitrogen removal from municipal wastewater: Removal performance, microbial community and mechanisms - Linhua Xie; Shuxin Wang; Yue Sun; Jia Li; Qiong Fan; Dan An; Minghua Ma (Journal of Water Process Engineering, 2024)

Effects of hydraulic cues in barrier environments on fish navigation downstream of dams - Lei Liao; Jia Li; Min Chen; Ruidong An (Journal of Environmental Management, 2024)

Current and future trends in the biocontrol of postharvest diseases - Xiaojiao Li; Shixian Zeng; Michael Wisniewski; Samir Droby; Longfeng Yu; Fuquan An; Yan Leng; Chaowen Wang; Xiaojun Li; Min He; Qinhong Liao; Jia Liu; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Fault diagnosis of wind turbine blade icing based on feature engineering and the PSO-ConvLSTM-transformer - Jicai Guo; Xiaowen Song; Shufeng Tang; Yanfeng Zhang; Jianxin Wu; Yuan Li; Yan Jia; Chang Cai; Qing'an Li (Ocean Engineering, 2024)

Exploring novel approaches to enhance start-up process in microbial fuel cell: A comprehensive review - Qianman Li; Yue Wang; Chenyun An; Hui Jia; Jie Wang (Journal of Water Process Engineering, 2024)

Developing novel ensemble models for predicting soil hydraulic properties in China’s arid region - Liantao Niu; Xiaoxu Jia; Xiangdong Li; Chunlei Zhao; Lidong Ren; Wei Hu; Ping Zhu; Danfeng Li; Baoqing Zhang; Ming'an Shao (Journal of Hydrology, 2024)

Molecular cloning and functional analyses of C–C motif chemokine ligand 3 (CCL3) in mandarin fish Siniperca chuatsi - Xiao Liu; Jia Xiang Ji; An Ning Pang; Li Li; Pin Nie; Li Qiang Zhang; Ke Wei Zeng; Shan Nan Chen (Fish & Shellfish Immunology, 2024)

Injectable biomimetic hybrid nanofibers for targeting cartilage in early osteoarthritis treatment - Maihemuti Yakufu; Qiyu Jia; Chunbao Li; Chuang Ma; Peng Zhang; Muyashaer Abudushalamu; Sajida Akber; Li Yan; Long Wang; Xinghua Song; Li Shu; Paerhati Wahafu; et al. (Chemical Engineering Journal, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Understanding the dilemmas and breakdown of the reactive migration of in situ groundwater injection reagents from an environmental geology perspective - Peng Wang; Jia Li; Pei An; Bingrui Yang; Deyi Hou; Shengyan Pu (Critical Reviews in Environmental Science and Technology, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Shifts in C-degradation genes and microbial metabolic activity with vegetation types affected the surface soil organic carbon pool - Qian Huang; Baorong Wang; Jikai Shen; Fengjing Xu; Na Li; Penghui Jia; Yongjian Jia; Shaoshan An; Isaac Dennis Amoah; Yimei Huang (Soil Biology and Biochemistry, 2024)

Early bearing fault diagnosis for imbalanced data in offshore wind turbine using improved deep learning based on scaled minimum unscented kalman filter - Hai-Hong Tang; Kun Zhang; Bing Wang; Xiao-jia Zu; You-Yi Li; Wu-Wei Feng; Xue Jiang; Peng Chen; Qing-An Li (Ocean Engineering, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Hollow glass microspheres incoporated conjugated microporous polymers composite aerogels for sustainable evaporation - Jiaxuan Zhou; Xiaoyin Cao; Yanju Jing; Jia Zhang; Hanxue Sun; Jiyan Li; Rui Jiao; An Li (Chemical Engineering Journal, 2024)

Citrus juice off-flavor during different processing and storage: Review of odorants, formation pathways, and analytical techniques - Xiao Jia; Jingnan Ren; Gang Fan; Gary A. Reineccius; Xiao Li; Nawei Zhang; Qi An; Qingshan Wang; Siyi Pan (Critical Reviews in Food Science and Nutrition, 2024)

Biodegradable plastics fragments induce positive effects on the decomposition of soil organic matter - Yanpei Li; Qing Yan; Jiao Wang; Ming’an Shao; Ziyan Li; Hanzhong Jia (Journal of Hazardous Materials, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Anisotropic materials based on carbohydrate polymers: A review of fabrication strategies, properties, and applications - Qi An; Jingnan Ren; Xiao Jia; Shasha Qu; Nawei Zhang; Xiao Li; Gang Fan; Siyi Pan; Zhifeng Zhang; Kangning Wu (Carbohydrate Polymers, 2024)

Suppression of neutrophil extracellular traps is responsible for the amelioration of chemotherapeutic intestinal injury by the natural compound PEITC - Mei Bai; Shuaifei Li; Cui Zhang; Ning An; Jie Wang; Jia Qin; Rumeng Jia; Wentao Liu; Jingcai Cheng; Xuefeng Wu; Qiang Xu (Toxicology and Applied Pharmacology, 2024)

Natural deep eutectic solvent: A promising eco-friendly food bio-inspired antifreezing - Xue Li; Jia-Ying Li; Muhammad Faisal Manzoor; Qiu-Ya Lin; Jia-ling Shen; Lan Liao; Xin-An Zeng (Food Chemistry, 2024)

Glass-cobalt Janus shell hollow microspheres: Shell structure dependence of mechanical strength and electromagnetic property - Qianqian Jia; Man Li; Zhenguo An; Ping Wang; Jingjie Zhang (Chemical Engineering Journal, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Response of soil water to long-term revegetation, topography, and precipitation on the Chinese Loess Plateau - Mingyu Chen; Xueqin Yang; Xutao Zhang; Yue Bai; Ming'an Shao; Xiaorong Wei; Yuhua Jia; Yunqiang Wang; Xiaoxu Jia; Yuanjun Zhu; Qingyin Zhang; Xuchao Zhu; et al. (CATENA, 2024)

Effect of different defects on the competitive adsorption of formaldehyde and water on the surface of carbon materials: Density functional theory study - Zhonghua Wang; Zekun Sun; Haiqian Zhao; Jun Li; Xing Zhang; Jiuyang Jia; Kaibo An; Ziyu Tang; Mingqi He; Zhibin Qu (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Exfoliated MXene/poly-melamine-formaldehyde composite membranes for removal of heavy metals and organics from aqueous solutions - Tian-Qi Zhang; Shuang Hao; Jun-Kai Zhao; Zhi-Qian Jia; Hong-Wei Tan; Yu Yang; Li-An Hou (Journal of Hazardous Materials, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

A comprehensive review of the promising clean energy carrier: Hydrogen production, transportation, storage, and utilization (HPTSU) technologies - Lei Zhang; Cunqi Jia; Fuqiao Bai; Wensen Wang; Senyou An; Kaiyin Zhao; Zihao Li; Jingjing Li; Hai Sun (Fuel, 2024)

Evolution law of wind-sand flow field of multi-row reed sand barriers and optimal spacing - Yuanfeng An; Jianjun Cheng; Lusheng Ding; Boyu Chen; Li Gao; Jia Lei; Benteng Ma; Zhipeng Zhen (Natural Hazards, 2024)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Driver’s visual luminance model considering the reflection characteristics of a tunnel’s inner wall: Theory and practice II - Shiyong He; Hao Liu; Pramod Bhusal; Lingna Shi; Jie Li; Jia'an Niu; Xianyun Cai; Bo Liang (Tunnelling and Underground Space Technology, 2023)

Rewiring Bacillus subtilis and bioprocess optimization for oxidoreductive reaction-mediated biosynthesis of D-tagatose - Guoyan Zhang; Yingfeng An; Hossain M Zabed; Junhua Yun; Amreesh Parvez; Mei Zhao; Cunsheng Zhang; Yuvaraj Ravikumar; Jia Li; Xianghui Qi (Bioresource Technology, 2023)

Circulating organochlorine pesticide levels, genetic predisposition and the risk of incident type 2 diabetes - Chengyong Jia; Shiyang Zhang; Xu Cheng; Peiwen Li; Jun An; Xin Zhang; Wending Li; Yali Xu; Handong Yang; Tao Jing; Huan Guo; Meian He (Environmental Pollution, 2023)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Early Ordovician to early Silurian forearc accretionary processes in front of the Selety–Stepnyak arc in the Kokchetav area, northern Kazakhstan: implications for continental growth in the northwestern Altaids - Xiaoliang Jia; Wenjiao Xiao; Miao Sang; Mingguo Zhai; Liang Li; Peng Huang; Shaole An; Qigui Mao; Zhou Tan; Hao Wang (International Journal of Earth Sciences, 2023)

Earthworm activity effectively mitigated the negative impact of microplastics on maize growth - Yanpei Li; Jiao Wang; Ming’an Shao; Hanzhong Jia (Journal of Hazardous Materials, 2023)

Lipid metabolic links between serum pyrethroid levels and the risk of incident type 2 diabetes: A mediation study in the prospective design - Chengyong Jia; Gaokun Qiu; Hao Wang; Shiyang Zhang; Jun An; Xu Cheng; Peiwen Li; Wending Li; Xin Zhang; Handong Yang; Kun Yang; Tao Jing; et al. (Journal of Hazardous Materials, 2023)

New insights into the regulation mechanism of Pacific white shrimp (Litopenaeus vannamei) hepatopancreas under 4-nonylphenol exposure using transcriptome analysis - Pei-Hua Zheng; Yao-Peng Lu; Xiu-Xia Zhang; Ke-Er Luan; Ze-Long Zhang; Jia-Jun Li; Tong Xu; Jun-Tao Li; Jian-An Xian; Hui Guo; An-Li Wang (Fish & Shellfish Immunology, 2023)

A structural similarity networking assisted collision cross-section prediction interval filtering strategy for multi-compound identification of complex matrix by ion-mobility mass spectrometry - Jia-Hui Wen; An-Qi Guo; Meng-Ning Li; Hua Yang (Analytica Chimica Acta, 2023)

Enhanced hydroxyl radical generation for micropollutant degradation in the In2O3/Vis-LED process through the addition of periodate - Tao Yang; Linqian An; Ge Zeng; Jiamin Mai; Yuying Li; Jinchuan Lian; Haochen Zhang; Juan Li; Xiaoxiang Cheng; Jianbo Jia; Minchao Liu; Jun Ma (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Insight into wavelength-dependent UVA-LED/chlorine process for micropollutant degradation: Performance, mechanism, and effects of water matrix - Ge Zeng; Jiamin Mai; Linqian An; Cui Huang; Juan Li; Haiping Wang; Qiuhua Li; Jingxin Yang; Xiaolong Xu; Changyu Liu; Jianbo Jia; Tao Yang; et al. (Chemical Engineering Journal, 2023)

Liquid-gas phase transition enables microbial electrolysis and H2-based membrane biofilm hybrid system to degrade organic pollution and achieve effective hydrogenotrophic denitrification of groundwater - Yu Han; Pinpin Yang; Yujie Feng; Naiyu Wang; Xiaole Yuan; Jingkun An; Jia Liu; Nan Li; Weihua He (Chemosphere, 2023)

The overlooked role of Cr(VI) in micropollutant degradation under solar light irradiation - Tao Yang; Cui Huang; Linqian An; Ge Zeng; Juan Li; Changyu Liu; Xiaolong Xu; Jianbo Jia; Jun Ma (Water Research, 2023)

Efficient removal of p-arsanilic acid and arsenite by Fe(II)/peracetic acid (Fe(II)/PAA) and PAA processes - Tao Yang; Linqian An; Ge Zeng; Maoju Jiang; Juan Li; Changyu Liu; Jianbo Jia; Jun Ma (Water Research, 2023)

Liquid-gas phase transition enables microbial electrolysis cell to treat organic pollution and synchronously remediate nitrate-contaminated groundwater via hydrogenotrophic denitrification - Yu Han; Yujie Feng; Naiyu Wang; Pinpin Yang; Guofang Ding; Jingkun An; Jia Liu; Nan Li; Weihua He (Journal of Cleaner Production, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

Unique Probiotic Properties and Bioactive Metabolites of Saccharomyces boulardii - JunJie Fu; Jun Liu; XuePing Wen; Guirong Zhang; Ji Cai; Zongwei Qiao; Zheming An; Jia Zheng; Li Li (Probiotics and Antimicrobial Proteins, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Nitric oxide induces defense responses in apple fruit against black spot disease caused by Alternaria alternata - Jie Han; Yingying Fan; Shicui Li; Binxin Jia; Jin Yang; Aibin Shen; Ting Dai; Jing An; Fengjuan Liu; Cheng Wang (South African Journal of Botany, 2023)

Identification of glucosinolates and volatile odor compounds in microwaved radish (Raphanus sativus L.) seeds and the corresponding oils by UPLC-IMS-QTOF-MS and GC × GC-qMS analysis - Xiao Jia; Pei Yu; Qi An; Jingnan Ren; Gang Fan; Zelan Wei; Xixiang Li; Siyi Pan (Food Research International, 2023)

Association between polychlorinated biphenyls exposure and incident type 2 diabetes mellitus: A nested case-control study - Peiwen Li; Yali Xu; Zhaoyang Li; Xu Cheng; Chengyong Jia; Shiyang Zhang; Jun An; Xin Zhang; Yan Yan; Meian He (Environmental Research, 2023)

One-pot solvothermal synthesis of Bi/Bi2S3/Bi2WO6 S-scheme heterojunction with enhanced photoactivity towards antibiotic oxytetracycline degradation under visible light - Jia Ding; Conghui Li; Huanshun Yin; Yunlei Zhou; Suo Wang; Kexue Liu; Min'an Li; Jun Wang (Environmental Pollution, 2023)

Facile synthesis of micro-eggette patterned nanofiltration membrane with enhanced anti-fouling and rejection performance - Wentao Shang; Wenjie Liu; Weiliang Wang; Noman Khalid Khanzada; Jiaxin Guo; Mu Li; Xiaoyan Li; Jia-Yong Lao; Shin Young Jeong; Chi Yan Tso; Feiyun Sun; Alicia Kyoungjin An (Desalination, 2023)

Structural characteristics and gel properties of pectin from citrus physiological premature fruit drop - Tingting Qi; Jingnan Ren; Xiao Li; Qi An; Nawei Zhang; Xiao Jia; Siyi Pan; Gang Fan; Zhifeng Zhang; Kangning Wu (Carbohydrate Polymers, 2023)

Juvenile hormone regulates the photoperiodic plasticity of elytra coloration in the ladybird Harmonia axyridis - Jia‐Xu Li; Zhong Tian; Xing‐Feng Liu; Bei Li; Hao‐Min An; Colin S. Brent; Jia‐Lu Wang; Xiao‐Ping Wang; Wen Liu (Molecular Ecology, 2023)
Many animals, including insects, exhibit plasticity of body colour in response to environmental changes. Varied expression of carotenoids, major cuticle pigments, significantly contributes to body colour flexibility. However, the molecular mechanisms by which environmental cues regulate carotenoid expression remain largely unknown. In this study, we used the ladybird Harmonia axyridis as a model to investigate the photoperiodic‐responsive plasticity of elytra coloration and its endocrine regulation. It was found that H. axyridis females under long‐day conditions develop elytra that are much redder than those under short‐day conditions, resulting from the differential accumulation of carotenoids. Exogenous hormone application and RNAi‐mediated gene knockdown indicate that carotenoid deposition was directed through the juvenile hormone (JH) receptor‐mediated canonical pathway. Moreover, we characterized an SR‐BI/CD36 ( SCRB ) gene SCRB10 as the carotenoid transporter responding to JH signalling and regulating the elytra coloration plasticity. Taken together, we propose that JH signalling transcriptionally regulates the carotenoid transporter gene for the photoperiodic coloration plasticity of elytra in the beetles, which reveals a novel role of the endocrine system in the regulation of carotenoid‐associated animal body coloration under environmental stimuli.

Euphorfinoids A and B, a pair of ent -atisane diterpenoid epimers from the roots of Euphorbia fischeriana, and their bioactivities - Jiang-Chun Wei; Yu-Ning Gao; Hui-Hui Huang; Xiao-Yu Zhang; Xuan-Li Liu; Xiao-Xu Gao; Na Li; Yue Zhao; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Molybdenum isotope evidence from restricted-basin mudstones for an intermediate extent of oxygenation in the late Ediacaran ocean - Zhaozhao Tan; Jinxiang Wu; Wanglu Jia; Jie Li; Brian Kendall; Jianzhong Song; Ping’an Peng (Chemical Geology, 2023)

Ecological risk assessment and ecological security pattern optimization in the middle reaches of the Yellow River based on ERI+MCR model - Lian’an Yang; Yali Li; Lujing Jia; Yongfan Ji; Guigui Hu (Journal of Geographical Sciences, 2023)

Neuropyrones A–E, five undescribed α-pyrone derivatives with tyrosinase inhibitory activity from the endophytic fungus Neurospora dictyophora WZ-497 - Xin Li; Yuan-Xiang Gong; Li Feng; Xin-Jia Wang; Jing-Wen Wang; An-Xin Zhang; Ning-Hua Tan; Zhe Wang (Phytochemistry, 2023)

Enhanced delivery of remedial reagents in low-permeability aquifers through coupling with groundwater circulation well - Peng Wang; Jia Li; Pei An; Zheng Yan; Yang Xu; Shengyan Pu (Journal of Hydrology, 2023)

The PER3rs772027021 SNP induces pigmentation phenotypes of dyschromatosis universalis hereditaria - Hongyu Chen; Pingping Yang; Dan Yang; Dongsheng Wang; Mao Lu; Yadong Li; Zhiqiang Zhong; Jing Zhang; Zhen Zeng; Zhi Liu; Xiaohua Zeng; Xu Jia; et al. (Journal of Molecular Medicine, 2023)

Evaluation of Fe3O4-MnO2@RGO magnetic nanocomposite as an effective persulfate activator and metal adsorbent in aqueous solution - Mang Lu; Xue-jiao Wu; Chu-xing Wan; Qiu-ping Gong; Jia-xin Li; Shuang-shuang Liao; Yu-an Wang; Shu-hao Yuan (Environmental Science and Pollution Research, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Livin promotes Th2-type immune response in airway allergic diseases - Yue Wang; Zhiyu Xiang; Miaomiao An; Huijing Jia; Chunyan Bu; Yanfeng Xue; Yao Wei; Ruiying Li; Xueping Qi; Fengli Cheng; Changqing Zhao; Jinmei Xue; et al. (Immunologic Research, 2022)
Objectives To investigate the effects of livin on the Th2 immune response in airway allergic diseases (AAD) and explore the interaction among livin, GATA3, IL-4 in peripheral blood CD4 + T cells of AAD patients. Methods WT mice and livin KO mice were developed for model of AAD. Th2 cell levels in the lung tissues and spleen were assessed by flow cytometry. Also, it was assessed in the culture after exposing to livin inhibitor (Lp-15); the protein and mRNA levels of livin, GATA3 and IL-4 in peripheral blood CD4 + T cells isolated from patients with or without AAD were measured by real-time quantitative polymerase chain reaction (RT-qPCR) and Western blotting, respectively. Finally, Co-immunoprecipitation (Co-IP) was employed to identify the interaction between livin and GATA3. Results Compared with WT mouse, Th2 cell frequency in lung tissues and spleen was significantly decreased in livin KO mouse; after adding Lp-15, the differentiation from Naive CD4 + T cells in spleen to Th2 cells was blocked; the protein and mRNA levels of livin, GATA3 and IL-4 in AAD group were higher than that in control group. The levels of livin were positively correlated with IL-4, and GATA3 was also positively correlated with IL-4 and livin. GATA3 was detected in the protein complex co-precipitated with livin antibody, and livin was also detected in the protein complex co-precipitated by GATA3 antibody. Conclusion Livin increases the expression of IL-4 and facilitates naive CD4 + T cells to differentiate into Th2 cells, which triggers airway allergy.

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Celsr3 Inactivation in the Brainstem Impairs Rubrospinal Tract Development and Mouse Behaviors in Motor Coordination and Mechanic-Induced Response - Boli Chen; Fuxiang Li; Bin Jia; Kwok-Fai So; Ji-An Wei; Yuchu Liu; Yibo Qu; Libing Zhou (Molecular Neurobiology, 2022)
Inactivation of Celsr3 in the forebrain results in defects of longitudinal axonal tracts such as the corticospinal tract. In this study, we inactivated Celsr3 in the brainstem using En1-Cre mice ( Celsr3 cKO) and analyzed axonal and behavioral phenotypes. Celsr3 cKO animals showed an 83% reduction of rubrospinal axons and 30% decrease of corticospinal axons in spinal segments, associated with increased branching of dopaminergic fibers in the ventral horn. Decreases of spinal motoneurons, neuromuscular junctions, and electromyographic signal amplitude of the biceps were also found in mutant animals. Mutant mice had impaired motor coordination and defective response to heavy mechanical stimulation, but no disability in walking and food pellet handling. Transsynaptic tracing demonstrated that rubrospinal axons synapse on spinal neurons in the deep layer of the dorsal horn, and mechanical stimulation of hindpaws induced strong calcium signal of red nuclei in control mice, which was less prominent in mutant mice. In conclusion, Celsr3 regulates development of spinal descending axons and the motor network in cell and non-cell autonomous manners, and the maturation of the rubrospinal system is required for motor coordination and response to mechanical stimulation.

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Quantitative detection of parasitic ciliate Cryptocaryon irritans in seawater with an optimized sample processing method - Jia‐Jia Tang; Zhi‐Hong Zhong; Zhi‐Cheng Li; Qing‐Kai Guo; Shi‐Yu Li; Yi‐Xuan Guo; Biao Jiang; An‐Xing Li (Journal of Fish Diseases, 2022)
The protozoan Cryptocaryon irritans is one of the most important ectoparasites of marine fish, causing ‘white spot disease’ and mass mortality in aquaculture. To accurately predict disease outbreaks and develop prevention strategies, improved detection methods are required that are sensitive, convenient and rapid. In this study, a pair of specific primers based on the C . irritans 18S rRNA gene was developed and used in a real‐time PCR (qPCR) assay. This assay was able to detect five theronts in 1 L of natural seawater. Furthermore, a linear model was established to analyse the log of Ct value and parasite abundance in seawater (y = –2.9623x + 24.2930), and the coefficient of determination (R 2 ) value was 0.979. A lysis buffer was optimized for theront DNA extraction and used for storage sample. This method was superior to the commercial water DNA kit, and there was no significant degradation of DNA at room temperature for 24–96 hr. A dilution method was developed to manage qPCR inhibitors and used to investigate natural seawater samples in a net cage farm with diseased fish, and the findings were consistent with the actual situation. This study provides a valuable tool for assisting in the early monitoring and control of cryptocaryoniasis in aquaculture.

The ecological mechanisms of Acetes blooms as a threat to the security of cooling systems in coastal nuclear power plants - Lina An; Lei Wang; Danyun Ou; Cun Jia; Weiwen Li; Ye Ding; Chengmao You; Jianji Liao; Hao Huang (Journal of Coastal Conservation, 2021)
Recently, there have been an increasing number of reports on the shutdown of coastal nuclear power plants because of outbreaks of marine organisms, such as jellyfish and fish. These organisms clog the pipes during an outbreak or when they accumulate near nuclear power plants in coastal regions. The safety of nuclear power plants is threatened by Acetes blooms. Thus, based on the physiology and ecology of Acetes , including the biology, auxology, feeding ecology, population dynamics, environmental suitability and effects of nuclear power plant thermal effluents, three hypotheses were proposed by previous studies to explain the ecological mechanisms of an Acetes bloom: (1) the wintering ground hypothesis, (2) the population dynamics hypothesis and (3) the ecosystem dynamics hypothesis. The main content and prevention measures used in previous studies were introduced and reviewed. Ecological protection combined with relevant environmental protection policies and laws in coastal areas are the long-term goals for the management of Acetes blooms.

Demographics of Scomberomorus commerson in the Central Taiwan Strait - Jinn-Shing Weng; Li-Chi Cheng; Yun-Sin Lo; Jen-Chieh Shiao; Jia-Sin He; Ming-An Lee; Kwang-Ming Liu (Journal of Marine Science and Engineering, 2021)
The narrow-barred Spanish mackerel Scomberomorus commerson is an economically essential species; however, few studies have investigated its demographic structure in the northwestern Pacific, which includes Taiwan’s waters. This study examined the growth parameters, age composition, mortality, and sex ratio of S. commerson catches by examining sagittal otoliths and other biological data collected in a 3-year project from June 2018 to June 2021. The transverse sections of sagittal otoliths exhibited alternating translucent and opaque zones, in annual cycles, and this observation was validated by otolith edge analysis. Opaque zones began to form in October; the growth peaked in December and lasted until March. Growth parameters were estimated for female (L∞ = 144.1 cm fork length [FL], k = 0.39 y−1, to = −0.85 y) and male (L∞ = 136.0 cm FL, k = 0.32 y−1, to = −1.49 y) specimens. The maximum recorded FL, body weight, and age were 159.0 cm, 27 kg, and 9.2 y for female and 135.0 cm, 17.8 kg, and 7.2 y for male specimens. Rapid growth was observed for both sexes, with FL reaching 66.8 ± 14.2 cm in female specimens and 70.1 ± 11.0 cm in male specimens during the first year of life. An age–length key based on the direct otolith aging and FL dataset (N = 646) was used to estimate the age composition of 3-year catches measured at landing (N = 16,133). The results verified that the S. commerson currently caught in the central Taiwan Strait are mainly young fish aged 1+ to 2+ y. The estimated fishing mortality (0.27 y−1) and exploitation rate (0.30) suggested that overfishing was not occurring in this stock. The findings of this study have helped clarify the population dynamics of the S. commerson in the Taiwan Strait, and the biological parameters reported herein can aid the management and conservation to ensure the sustainability of this species in this region.

Resting-state abnormalities in functional connectivity of the default mode network in autism spectrum disorder: a meta-analysis - Qing Wang; Hua-Yun Li; Yun-Da Li; Ya-Ting Lv; Hui-Bin Ma; An-Feng Xiang; Xi-Ze Jia; Dong-Qiang Liu (Brain Imaging and Behavior, 2021)

A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis - Shi-Ying Mai; Yong-Hui Li; Xu-Guang Zhang; Yi-Ran Wang; Jun-Qing Zhang; An Jia (Natural Product Research, 2021)

Deficiency of Klc2 Induces Low-Frequency Sensorineural Hearing Loss in C57BL/6 J Mice and Human - Xiaolong Fu; Yachun An; Hongyang Wang; Peipei Li; Jing Lin; Jia Yuan; Rongyu Yue; Yecheng Jin; Jiangang Gao; Renjie Chai (Molecular Neurobiology, 2021)

A new species of Pacifides from the Western Pacific Coast and the first fully freshwater species of the maricolan planarian genus Paucumara (Platyhelminthes, Tricladida, Maricola) - Ming-Yi Li; Xin-Yi Ma; Wei-Xuan Li; Ying Yang; Ronald Sluys; Jia-Jia Chen; Shuang-Fei Li; An-Tai Wang (Systematics and Biodiversity, 2021)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

The regional difference in engineering-control and tillage factors of Chinese Soil Loss Equation - Rui-yin Chen; Dong-chun Yan; An-bang Wen; Zhong-lin Shi; Jia-cun Chen; Yuan Liu; Tai-li Chen (Journal of Mountain Science, 2021)

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Dorsolateral Striatal proBDNF Improves Reversal Learning by Enhancing Coordination of Neural Activity in Rats - Wei Sun; Hongxia Che; Jia Li; Dongxin Tang; Xiaoyun Liu; Wenhui Liu; Lei An (Molecular Neurobiology, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Effects of Sulfamethoxazole Exposure on the Growth, Antioxidant System of Chlorella vulgaris and Microcystis aeruginosa - Xiaotong Dong; Shaohua Sun; Ruibao Jia; Lirong Xu; Wei Hou; Nannan Lu; Mingquan Wang; Qinghua Zhao; Li’an Hou (Bulletin of Environmental Contamination and Toxicology, 2020)

Genesis of the Linghu Au deposit in Xiaoqinling Region, Henan province, China: Constraints from fluid inclusions and isotope systematics - Wei Zeng; Zhi-gao Wang; Duo Wan; Feng-yue Sun; Cheng-dong Li; Reng-an Yu; Jia-ying Wang; Jian-chang Xu (Arabian Journal of Geosciences, 2020)

Study on the removal of humic acid by ultraviolet/persulfate advanced oxidation technology - Guangxue Ji; Shaohua Sun; Ruibao Jia; Jianguang Liu; Zhenxing Yao; Mingquan Wang; Qinghua Zhao; Li’an Hou (Environmental Science and Pollution Research, 2020)

Antioxidant coumarin and pyrone derivatives from the insect-associated fungus Aspergillus Versicolor - Tian-Xiao Li; Dan-Dan Meng; Ying Wang; Jin-Lu An; Jia-Feng Bai; Xue-Wei Jia; Chun-Ping Xu (Natural Product Research, 2020)

Comparative study on the bioaccumulation of lead, cadmium and nickel and their toxic effects on the growth and enzyme defence strategies of a heavy metal accumulator, Hydrilla verticillata (L.f.) Royle - Hong Zhang; Ling-Lei Zhang; Jia Li; Min Chen; Rui-Dong An (Environmental Science and Pollution Research, 2020)

Experimental study on the physical modeling of loess tunnel-erosion rate - Li Wang; Xi-An Li; Lin-Cui Li; Bo Hong; Jia Liu (Bulletin of Engineering Geology and the Environment, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Giant Submarine Landslide in the South China Sea: Evidence, Causes, and Implications - Chaoqi Zhu; Sheng Cheng; Qingping Li; Hongxian Shan; Jing’an Lu; Zhicong Shen; Xiaolei Liu; Yonggang Jia (Journal of Marine Science and Engineering, 2019)
Submarine landslides can be tremendous in scale. They are one of the most important processes for global sediment fluxes and tsunami generation. However, studies of prodigious submarine landslides remain insufficient. In this review paper, we compile, summarize, and reanalyze the results of previous studies. Based on this reanalysis, we discover the giant Baiyun–Liwan submarine slide in the Pearl River Mouth Basin, South China Sea. We describe three concurrent pieces of evidence from ~23 Ma to 24 Ma, the Oligocene–Miocene boundary, for this landslide: the shoreward shift of the shelf break in the Baiyun Sag, the slump deposition to the southeast, and the abrupt decrease in the accumulation rate on the lower continental slope. This landslide extends for over 250 km, and the total affected area of the slide is up to ~35,000–40,000 km2. The scale of the landslide is similar to that of the Storegga slide, which has long been considered to be the largest landslide on earth. We suggest that strike–slip movement along the Red River Fault and ridge jump of the South China Sea caused the coeval Baiyun–Liwan submarine slide. The identification of the giant landslide will promote the understanding of not only its associated geohazards but also the steep rise of the Himalayan orogeny and marine engineering. More attention needs to be paid to areas with repeated submarine landslides and offshore installations.

OsRhoGAP2 promoter drives inflorescence-preferential expression and confers responses to abiotic stresses in transgenic Arabidopsis - Junjun Huang; Xintian Yan; Jiajia Li; Jia Shi; Jingjing Peng; Jingyao Du; Huiwen Ge; Meina Wang; Wenjing An; Kaijie Wang; Huahua Wang; Weihong Liang (Acta Physiologiae Plantarum, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

Stability analysis unit and spatial distribution pattern of the terrain texture in the northern Shaanxi Loess Plateau - Hu Ding; Jia-ming Na; Xiao-li Huang; Guo-an Tang; Kai Liu (Journal of Mountain Science, 2018)

Release and kinetics of arsenic and plumbum in the Songhua River surficial sediments - Guang-Min Liu; Qing An; Li-Juan Wang; Xin Jia; Si-Hui Feng; Shu-Mei Xia; Yi-Ning Wu; Hong Qi (Environmental Science and Pollution Research, 2018)

The growth inhibitory effects of garlic polysaccharide combined with cis-dichlorodiamine platinum on human HepG2 cells - Liyan Li; Tao Huang; Chong Lan; An Jia; Yang Mao (Biologia, 2017)

Genome-wide identification, characterization, and expression analysis of SnRK2 family in Hevea brasiliensis - Dong Guo; Hui-Liang Li; Jia-Hong Zhu; Ying Wang; Feng An; Gui-Shui Xie; Shi-Qing Peng (Tree Genetics & Genomes, 2017)

Identification and functional characterization of DzS3GT, a cytoplasmic glycosyltransferase catalyzing biosynthesis of diosgenin 3-O-glucoside in Dioscorea zingiberensis - Ting Ye; Wei Song; Jia-Jiao Zhang; Mei An; Shan Feng; Shan Yan; Jiaru Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Removal of Congo red from aqueous solution by adsorption onto different amine compounds modified sugarcane bagasse - Jun-xia Yu; Wan-li Xiong; Jing Zhu; Jia-dong Chen; Ru-an Chi (Clean Technologies and Environmental Policy, 2017)

Two comparative approaches to identify the conservation priority areas impacted by heavy metals on Yellow Sea coasts - Ning Li; Wen Yang; Lingqian Xu; Xiaobo Jia; Shuqing An; Shubo Fang (Journal of Coastal Conservation, 2017)

Expression of KCNA5 Protein in Human Mammary Epithelial Cell Line Associated with Caveolin-1 - Jia Liu; Chao Qu; Hongyan Li; Yejun Zhang; Jia Sun; Shuo Yang; Jing Liu; Lijia An; Wei Zou (The Journal of Membrane Biology, 2016)

Effect of operation parameters on the flux stabilization of gravity-driven membrane (GDM) filtration system for decentralized water supply - Xiaobin Tang; An Ding; Fangshu Qu; Ruibao Jia; Haiqing Chang; Xiaoxiang Cheng; Bin Liu; Guibai Li; Heng Liang (Environmental Science and Pollution Research, 2016)

Amentoflavone protects against psoriasis-like skin lesion through suppression of NF-κB-mediated inflammation and keratinocyte proliferation - Jingang An; Zhengxiao Li; Yingying Dong; Jianwen Ren; Jia Huo (Molecular and Cellular Biochemistry, 2016)

Hyperspectral field estimation and remote-sensing inversion of salt content in coastal saline soils of the Yellow River Delta - Deyu An; Gengxing Zhao; Chunyan Chang; Zhuoran Wang; Ping Li; Tongrui Zhang; Jichao Jia (International Journal of Remote Sensing, 2016)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Methylopila henanense sp. nov., a novel methylotrophic bacterium isolated from tribenuron methyl-contaminated wheat soil - Ya-Nan Wang; Wen-Yu Tian; Wei-Hong He; Guo-Can Chen; Ming-Li An; Bin Jia; Li Liu; Yang Zhou; Shuang-Jiang Liu (Antonie van Leeuwenhoek, 2015)

E2F1 regulates p53R2 gene expression in p53-deficient cells - Jun-Juan Qi; Ling Liu; Ji-Xiang Cao; Guo-Shun An; Shu-Yan Li; Gang Li; Hong-Ti Jia; Ju-Hua Ni (Molecular and Cellular Biochemistry, 2015)

Response of soil CO2 efflux to water addition in temperate semiarid grassland in northern China: the importance of water availability and species composition - Xiaoxu Jia; Ming’an Shao; Xiaorong Wei; Xuezhang Li (Biology and Fertility of Soils, 2014)

A Magnetic Nanoparticle Stabilized Gas Containing Emulsion for Multimodal Imaging and Triggered Drug Release - Wei Guo; Diancheng Li; Jia-an Zhu; Xiaohui Wei; Weiwei Men; Dazhi Yin; Mingxia Fan; Yuhong Xu (Pharmaceutical Research, 2014)

Erratum to: Haploid plants from anther cultures of poplar (Populus × beijingensis) - Ying Li; Hao Li; Zhong Chen; Le-Xiang Ji; Mei-Xia Ye; Jia Wang; Lina Wang; Xin-Min An (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

E2F1-mediated DNA damage is implicated in 8-Cl-adenosine-induced chromosome missegregation and apoptosis in human lung cancer H1299 cells - Yu-Ying Han; Zhe Zhou; Ji-Xiang Cao; Ya-Qiong Jin; Shu-Yan Li; Ju-Hua Ni; Guo-Shun An; Yu-Xiang Zhang; Hong-Ti Jia (Molecular and Cellular Biochemistry, 2013)

Temporal Modulation of Sodium Current Kinetics in Neuron Cells by Near-Infrared Laser - Xinyu Li; Jia Liu; Shanshan Liang; Kuiwen Guan; Lijia An; Xuefei Wu; Shao Li; Changsen Sun (Cell Biochemistry and Biophysics, 2013)

Impacts of Urbanization and Station-relocation on Surface Air Temperature Series in Anhui Province, China - Yuan-Jian Yang; Bi-Wen Wu; Chun-e Shi; Jia-Hua Zhang; Yu-Bin Li; Wei-An Tang; Hua-Yang Wen; Hong-Qun Zhang; Tao Shi (Pure and Applied Geophysics, 2013)

Seasonally variable intestinal metagenomes of the red palm weevil ( R hynchophorus ferrugineus ) - Shangang Jia; Xiaowei Zhang; Guangyu Zhang; An Yin; Sun Zhang; Fusen Li; Lei Wang; Duojun Zhao; Quanzheng Yun; Tala; Jixiang Wang; Gaoyuan Sun; et al. (Environmental Microbiology, 2013)
Summary The intestinal microbes residing in the red palm weevil ( RPW , R hynchophorus ferrugineus ) larva consume tender interior fibrous tissues of date palm trunks. The understanding of such microbiota at molecular level provides vital clues for the biological control of this devastating pest. Using pyrosequencing and shotgun strategy, we first study taxonomic profiles of the microbiota sampled at different months ( M arch, J uly and N ovember), and then confirm the impact of high‐temperature stress on the microbial populations based on data from 16S rRNA amplicons using both field and laboratory samples. We further identify K lebsiella pneumoniae in N ovember and L actococcus lactis in J uly as the dominant species of the microbiota. We find that the RPW gut microbiota degrades polysaccharides and sucrose with hydrolases and that different active bacterial species in N ovember and J uly are responsible for the symbiotic relationship between the microbiota and the host. Our results provide vital information for pest control and cellulolytic bacterial species characterization.

Haploid plants from anther cultures of poplar (Populus × beijingensis) - Ying Li; Hao Li; Zhong Chen; Le-Xiang Ji; Mei-Xia Ye; Jia Wang; Lina Wang; Xin-Min An (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Genomewide analysis of the chitinase gene family in Populus trichocarpa - CONG JIANG; RUI FANG HUANG; JIA LIANG SONG; MIN REN HUANG; LI AN XU (Journal of Genetics, 2013)

Expression of survivin and patients survival in non-small cell lung cancer: a meta-analysis of the published studies - Li-nian Huang; Dong-sheng Wang; Yu-qing Chen; Cheng-ling Zhao; Bei-lei Gong; An-bang Jiang; Wei Jia; Feng-dan Hu (Molecular Biology Reports, 2013)

A simple method to prepare magnetic modified beer yeast and its application for cationic dye adsorption - Jun-Xia Yu; Li-Yan Wang; Ru-An Chi; Yue-Fei Zhang; Zhi-Gao Xu; Jia Guo (Environmental Science and Pollution Research, 2013)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

Genetic variants of the MRC1 gene and the IFNG gene are associated with leprosy in Han Chinese from Southwest China - Dong Wang; Jia-Qi Feng; Yu-Ye Li; Deng-Feng Zhang; Xiao-An Li; Qing-Wei Li; Yong-Gang Yao (Human Genetics, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Precise mapping Fhb5, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Mingzhi Tang; Yan Zhou; Guoqiang Li; Xia An; Feng Lin; Haibin Xu; Haiyan Jia; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2011)

Benefits of a symbiotic association with endophytic fungi are subject to water and nutrient availability in Achnatherum sibiricum - An Zhi Ren; Xia Li; Rong Han; Li Jia Yin; Mao Ying Wei; Yu Bao Gao (Plant and Soil, 2011)

Fine mapping Fhb4, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Guoqiang Li; Haiyan Jia; Feng Xu; Feng Lin; Mingzhi Tang; Yao Wang; Xia An; Haibin Xu; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2010)

Optimization of soybean (Glycine max (L.) Merrill) in planta ovary transformation using a linear minimal gus gene cassette - Ming Liu; Jun Yang; Yun-qing Cheng; Li-jia An (Journal of Zhejiang University-SCIENCE B, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Passive Protection Assay of Monoclonal Antibodies Against Dengue Virus in Suckling Mice - Zongtao Chen; Li-Mei Liu; Na Gao; Xiao-Feng Xu; Jun-Lei Zhang; Jia-Li Wang; Jing An (Current Microbiology, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Molecular Identification of cDNA, Immunolocalization, and Expression of a Putative Odorant-Binding Protein from an Asian Honey Bee, Apis cerana cerana - Hong-Liang Li; Ya-Li Zhang; Qi-Kang Gao; Jia-An Cheng; Bing-Gan Lou (Journal of Chemical Ecology, 2008)

Vimentin is required for dengue virus serotype 2 infection but microtubules are not necessary for this process - Wei Chen; Na Gao; Jia-li Wang; Yan-ping Tian; Zong-tao Chen; Jing An (Archives of Virology, 2008)

Phytase expression in transgenic soybeans: stable transformation with a vector-less construct - Xiao Rong Gao; Guo Kun Wang; Qiao Su; Yan Wang; Li Jia An (Biotechnology Letters, 2007)

AtMTM1, a novel mitochondrial protein, may be involved in activation of the manganese-containing superoxide dismutase in Arabidopsis - Zhao Su; Mao-Feng Chai; Ping-Li Lu; Rui An; Jia Chen; Xue-Chen Wang (Planta, 2007)

Mutation induced by ethylmethanesulphonate (EMS), in vitro screening for salt tolerance and plant regeneration of sweet potato (Ipomoea batatas L.) - Yu-Shi Luan; Juan Zhang; Xiao-Rong Gao; Li-Jia An (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Molecular cloning and characterization of betaine aldehyde dehydrogenase gene from Suaeda liaotungensis and its use in improved tolerance to salinity in transgenic tobacco - Qiu-Li Li; Xiao-Rong Gao; Xiao-Hong Yu; Xing-Zhi Wang; Li-Jia An (Biotechnology Letters, 2003)

Enhancing ethanol tolerance of a self-flocculating fusant of Schizosaccharomyces pombe and Saccharomyces cerevisiae by Mg2+ via reduction in plasma membrane permeability - Chun-Keng Hu; Feng-Wu Bai; Li-Jia An (Biotechnology Letters, 2003)